Association between different dimensions of anger and symptoms of post-traumatic stress disorder in at-risk cardiovascular patients during the COVID-19 pandemic - Nesic, Mihailo; Vogel, Julia; Krüger, Jan Philipp; Wenzel, Werner; Sahebi, Ali; Rassaf, Tienush; Siebermair, Johannes; Wesemann, Ulrich (Frontiers in Psychiatry, 2023)
Introduction: The common connecting factor between post-traumatic stress disorder (PTSD) and cardiovascular diseases lies in the disruption of the stress processing system. The influence of anger on cardiovascular diseases has hardly been investigated so far. The focus of this study is on anger regulation in cardiovascular risk patients. The COVID-19 pandemic is considered as an additional stressor in this study, but not as a separate entity. The hypothesis is that individuals with inward anger are more prone to PTSD. Methods: As part of the routine examination, all patients who were hospitalized between January 1st, 2021 and May 31st, 2022 with high-risk cardiovascular diseases were included. A total of N = 153 (84.1%) subjects participated in the study. On admission, anger (STAXI-2) and PTSD (PCL-5) were assessed using questionnaires. The relationship between different domains of anger and post- traumatic stress symptoms was examined. Results: Inwardly directed anger was more pronounced in this population than in a standard sample (+1 SD) and had a significant impact on the presence of PTSD (B=- .72, p<.001). Additionally, correlations were found between inward-directed anger and PTSD, as well as all other anger expressions studied and the PTSS total score. Discussion: It can be assumed that anger and its regulation are relevant factors for both cardiac diseases and PTSD. The study results can be used for prevention, rehabilitation and therapeutic measures. However, the impact of inner anger on PTSD is theoretical and based on statistical testing. A confirmatory longitudinal study is needed to substantiate these results.